2006
DOI: 10.1055/s-2005-865836
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Exercise-Induced Leptin Suppression Associated with Insufficient Epinephrine Reserve in Patients with Classic Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency

Abstract: CAH patients do not manifest exercise-induced leptin suppression. The most probable reason for this is their severely impaired epinephrine stress response. In addition, epinephrine deficiency is leading to secondary changes in various catecholamine dependent metabolic pathways, e. g., energy balance. Although obvious clinical sequelae are so far unknown, the catecholamine-deficient state and the resulting hyperleptinemia might contribute to the severity of the disease in CAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Even a small increment of a few beats per minute within the normal range can increase the cardiovascular risk (28). Our younger patients had normal heart rates in accord with previous studies of young patients (29)(30)(31). The heart rate in CAH males was correlated with other cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Even a small increment of a few beats per minute within the normal range can increase the cardiovascular risk (28). Our younger patients had normal heart rates in accord with previous studies of young patients (29)(30)(31). The heart rate in CAH males was correlated with other cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 78%
“…Epinephrine production has been shown to be impaired in adolescents and young adults with classic CAH (1,(29)(30)(31). This defect is certainly the result of insufficient prenatal cortisol secretion from the adrenal cortex, necessary for adrenomedullary organogenesis and epinephrine production (1).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, plasma epinephrine and urine MN levels were similar in the CAH subgroups. Compensatory increases in sympathetic nerve activity resulting in an increase in NE secretion have been reported in adrenalectomized patients [20] and patients with Addison’s disease [21], but not in patients with CAH [4,22,23]. Zuckerman-Levin et al [15] found that resting and stimulated NE levels in patients with isolated glucocorticoid deficiency tended to be higher compared with control subjects, but these did not reach statistical significance when compared with the control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several publications have described the negative impact that 21-hydroxylase deficiency has on adrenal medullary development [8], and it has been demonstrated that CAH patients have a compromised catecholamine reserve that results in a diminished catecholamine response to stress [41, 42]. To date, these studies have not led to any firm therapeutic consequences.…”
Section: Experimental Therapies In Cahmentioning
confidence: 99%